The Relationship between Internal Supervision Process and Teaching Efficiency of Teachers in Schools under Khon Kaen Secondary Educational Service Area Office - Wilailert, Ruckiat; Piampuechana, Niyada (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of the research on the relationship between internal supervision process and teaching efficiency of teachers in schools under Khon Kaen Secondary Educational Service Area Office were 1) to study the internal supervision process in schools, 2) to study teaching efficiency of teachers in schools, and 3) to study the relationship between internal supervision process and teaching efficiency of teachers in schools under Khon Kaen Secondary Educational Service Area Office, classified by school’s size and work experience. This research was correlational research type. The sample group used in the research consisted of administrators and teachers of schools, with the total number of 356 people. This research was calculated by using Taro Yamane’s formula at a sampling error level of 0.05, using stratified random sampling method. The research instrument was a 5-level rating scale questionnaire with a content validity of 0.67 – 1 and a questionaire with reliability of 0.97 for the entire questionnaire. The statistics used for data analysis comprised percentage, mean, standard deviation, and Pearson’s product moment correlation coefficient. The research results were as follows: 1. The internal supervision process under Khon Kaen Secondary Educational Service Area Office, in overall, was rated at a high level. 2. Teaching efficiency of teachers in schools under Khon Kaen Secondary Educational Service Area Office, in overall, was rated at a high level of performance. 3. The relationship between the internal supervision process and teaching efficiency of teachers in schools under Khon Kaen Secondary Educational Service Area Office, in overall, was positive and rated at a high level with statistical significance at 0.01 level.